Adolescents in public housing : addressing psychological and behavioral health - Nebbitt, Von E. (EBL-Schweitzer, 2015)
'Adolescents in Public Housing' incorporates data from multiple public-housing sites in large U.S. cities to shine much-needed light on African American youth living in non-HOPE VI public-housing neighbourhoods. With findings grounded in research, the book gives practitioners and policy makers a solid grasp of the attitudes toward deviance, alcohol and drug abuse, and depressive symptoms characterizing these communities, and links them explicitly to gaps in policy and practice.